Public Goods, Self-Selection and Optimal Income Taxation - Robin Boadway; Michael Keen (Queen's University, Department of Economics, 1991)
Using the self-selection approach to tax analysis, this paper derives a modified Samuelson Rule for the provision of public goods when the government deploys an optimal non-linear income tax. This approach gives a straightforward interpretation of the central result in this area, generalizes it , and provides a simple characterization of optimal policy in a wide range of circumstances.
Keywords: 330